2022
DOI: 10.1007/s00586-022-07327-3
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus open surgery for degenerative lumbar pathologies:a systematic review and meta-analysis

Abstract: Introduction With the increase in life expectancy and consequent aging of the population, degenerative lumbar spine diseases tend to increase its number exponentially. Several treatment options are available to treat degenerative spinal diseases, such as laminectomies, posterior fusions, and interbody fusions, depending on their locations, correction necessities, and surgeon philosophy. With the advance in technology and surgical knowledge, minimally invasive techniques (MIS) arose as a solution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We found no difference in GRS grade between screws placed through Wiltse and open-midline incisions. However, according to previous published work, 14 the minimally invasive Wiltse approach is associated with significantly less blood loss (median 150.0 cc (IQR 100.0 to 250.0) vs 300.0 (IQR 150.0 to 440.0)) and a decreased length of hospital stay (3.0 days (IQR 2.0 to 5.0) vs 4.0 (IQR 3.0 to 5.75)), but with similar operating times, and may therefore be a valuable surgical option in RNA without compromising the accuracy of screw placement.…”
Section: Discussionmentioning
confidence: 90%
“…We found no difference in GRS grade between screws placed through Wiltse and open-midline incisions. However, according to previous published work, 14 the minimally invasive Wiltse approach is associated with significantly less blood loss (median 150.0 cc (IQR 100.0 to 250.0) vs 300.0 (IQR 150.0 to 440.0)) and a decreased length of hospital stay (3.0 days (IQR 2.0 to 5.0) vs 4.0 (IQR 3.0 to 5.75)), but with similar operating times, and may therefore be a valuable surgical option in RNA without compromising the accuracy of screw placement.…”
Section: Discussionmentioning
confidence: 90%
“…When conservative treatments, such as medication and physiotherapy, prove inadequate, surgical intervention is frequently necessary. [23] The lumbar non-fusion approach has given rise to the interspinous fixation system, which has become a widely utilized clinical option. This includes a variety of options such as static distraction systems (such as Wallis, X-STOP), dynamic stabilization systems (such as Coflex, DIAM, StenoFix), and innovative percutaneous implantable stability systems (such as Aperius, Superion, In-Space).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has a satisfactory clinical outcome when treating lumbar spinal stenosis, traditional open surgery can cause paravertebral muscle dissection, signi cant bleeding, and postoperative lumbar spine instability [3] . More research has demonstrated in recent years that uniportal endoscopy can treat lumbar spinal stenosis with clinical outcomes that are comparable to open surgery while requiring a smaller incision, less damage to the paravertebral muscle and spinal column bone structure, and a quicker recovery [4][5][6][7][8] .However, uniportal endoscopy (UE) has limits on surgical equipment, as the supporting surgical instruments are often small and the decompression time is prolonged. Currently, unilateral biportal endoscopy (UBE) technology is gaining popularity.…”
Section: Introductionmentioning
confidence: 99%